A preliminary study of students and industrial acceptance of the work from home (wfh) method during the covid-19 pandemic in Malaysia / Farah Wahida Mohd Latib …[et al.] - Mohd Latib, Farah Wahida; Nazarudin, Ainamardia; Tholibon, Duratul Ain; Ab Latif, Amminudin; Othman, Zulhafizal; Bachok, Mohd Fairuz; Abdul Rahman, Abdul Samad (Universiti Teknologi MARA Cawangan Pahang, 2021)
This study is to identify the students and industrial acceptance and possible approach toward the implementing work from home (WFH) method during the third, fourth & conditional Movement Control Order (CMCO) phase and their level of readiness for this method. A preliminary survey of their acceptance of this method has been conducted focusing on students undergoing Industrial Training (IT) course (ECM377), Diploma in Civil Engineering UiTM, EC110, using a non-probability convenience sampling method. There were three campuses involved in this study which are FCE UiTM Cawangan Pahang, Cawangan Sarawak, and Cawangan Johor. The collected data were analyzed using the percentage value and results found that most of the industry and students do not agree to undergo IT with the WFH method. The main reason given by them is as they gain less experience if working from home. If students are not allowed to WFH, students must postpone their studies, which will result the extension of their study. Therefore, this preliminary study is needed to allow faculty to plan an action that can be taken to solve these issues so that students can complete the IT course and at the same time good relations with the industry continue to be established.